MO301RITUXIMAB FOR RELAPSING MEMBRANOUS NEPHROPATHY: A SPANISH HOSPITAL EXPERIENCE. (29th May 2021) - Fernandez Lorente, Loreto; Manrique, Joaquin; Visus, Maria Teresa; Izquierdo, Diana; Castaño, Itziar; Slon Roblero, Maria Fernanda; Gomez, Nerea; Romero, Gregorio; Purroy Iruzun, Carolina
Abstract: Background and Aims: B cell targeting agent Rituximab has been proven to be effective and safe for the treatment of idiopathic membranous nephropathy (iMN) in previous studies with nearly 75% achievement of partial or complete remission of nephrotic syndrome. The aim of this study was to evaluate this treatment in a cohort of patients at Complejo Hospitalario de Navarra with relapsing disease. Method: This is a retrospective, cross sectional study including 12 patients with membranous nephropathy diagnosed by means of a kidney biopsy. All of them were treated before with different immunosuppressive regimens and had a relapse at the time of the inclusion. All of them were treated with two iv infusions of Rituximab. In this study we report patient clinical and immunological baseline characteristics and treatment response at 12 months of follow up. Results: Between 2015-20 a total of 12 patients (41, 6% women and 58, 3% men) were treated with two iv infusions of Rituximab with a total mean dose of 2gr. All of them diagnosed previously of iMN, and 10/12 were PLA2r positive. Baseline laboratory data showed serum creatinine levels 1, 3±0, 9 mg/dl, serum albumin 29±9 g/L, 24 hour- urinary protein excretion of 6, 8±3, 2 and serum PLA2R levels of 50, 54±63, 2 RU/ml. Either complete or partial response (CR and PR) were achieved in 83, 3% of the cases, however only 3/12 (25%) patients had a complete response at 12 months follow up. All patients who responded had also a significative decrease PLA2r antibodies. Three of the patients who did a PR were treated with an incomplete dose of iv Rituximab (two infusions of 500mg). Conclusion: Rituximab was effective in our cohort of patients with iMN with achievement of 83, 3% response at 12 months of follow up, however only 25% of patients had complete response maybe due to incomplete dosing. Immunological response was seen in all patients. Still, a longer follow up of these patients is needed in order to evaluate Rituximab response.